1991
DOI: 10.1084/jem.174.3.613
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies that are specific for a single amino acid interchange in a protein epitope use structurally distinct variable regions.

Abstract: SummaryWe have analyzed how the immune system generates antibodies that are specific for analogues of an epitope on the influenza virus hemagglutinin (HA) that differ solely by the presence of Asp or Gly at amino acid 225 . Most antibodies induced in response to HA(Asp225) use one of a few closely related variable (V) region structures that are encoded by characteristic VH/Vk gene segment combinations. Remarkably, none of these VH/Vk combinations was induced in response to HA(Gly225) . Instead of modifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…We previously showed that the majority of the Ab response to the T3 HA in BALB/c mice cross-reacts with the PR8 HA, while ϳ15% is directed to epitopes that include aa 225, uses structurally distinct variable regions, and does not cross-react with the PR8 HA (38). To examine the effects of the neo self-PR8 HA on B cell repertoire formation, we immunized HACII, HA104, and BALB/c mice with T3 virus and determined the frequency of B cells that can react with T3 and PR8 viruses.…”
Section: Use Of Mutant Virus Immunization To Examine B Cell Tolerancementioning
confidence: 99%
“…We previously showed that the majority of the Ab response to the T3 HA in BALB/c mice cross-reacts with the PR8 HA, while ϳ15% is directed to epitopes that include aa 225, uses structurally distinct variable regions, and does not cross-react with the PR8 HA (38). To examine the effects of the neo self-PR8 HA on B cell repertoire formation, we immunized HACII, HA104, and BALB/c mice with T3 virus and determined the frequency of B cells that can react with T3 and PR8 viruses.…”
Section: Use Of Mutant Virus Immunization To Examine B Cell Tolerancementioning
confidence: 99%
“…The H-and L-chain V regions of the hybridoma Abs were sequenced from mRNA according to the protocol described (23). Briefly, cytoplasmic RNA was isolated and constant region-specific primers were used to direct synthesis of cDNA copies of the H-(C1) and L-(C1 and C) chain V regions.…”
Section: Sequence Analysismentioning
confidence: 99%
“…Briefly, cytoplasmic RNA was isolated and constant region-specific primers were used to direct synthesis of cDNA copies of the H-(C1) and L-(C1 and C) chain V regions. The cDNA was then amplified using the constant region primers in conjunction with VH5Ј1 for H-chains and 1L or L5 primers for Lchains (23). Amplification products were sequenced by automated analysis (The Wistar Institute Nucleic Acid Facility).…”
Section: Sequence Analysismentioning
confidence: 99%
“…For example, antibodies against a(I -•6) dextrans use difTerent VH and VL genes to form combining sites specific for the inlernal linear sequence [27], Diverse V,i and V] genes can be used to produce antibodies reactive with a defined protein epitope [28]. Also, two structurally different antibodies have been characterized that are specific for an epitope of the infiuenza virus haemagglutinin protein different for only one amino acid [29], Although the epitope in ihis case was very similar, the antibodies were shown to lie structurally very different.…”
Section: Discussionmentioning
confidence: 99%